Anorectal Gastrointestinal Stromal Tumor: A Case Report and Literature Review. (25th March 2013) - Singhal, Sanjeev; Singhal, Anu; Tugnait, Rahul; Varghese, Vineet; Tiwari, Bishwanath; Arora, Pankaj K.; Malik, Pawan; Bharali, Mriganka Deuri; Dhuria, Ankur Subhash; Chauhan, Pushkar; Singh, Chandrakant; Ballani, Amit; et al.
Abstract : Gastrointestinal stromal tumors or "GIST" are mesenchymal neoplasms expressing KIT(CD117) tyrosine kinase and showing the presence of activating mutations in KIT or PDGFR α (platelet-derived growth factor alpha). GIST of anal canal is an extremely rare tumor, accounting for only 3% of all anorectal mesenchymal tumors and 0.1–0.4% of all GIST. GIST with large tumor size and high mitotic activity are highly malignant, but the biological behavior of anorectal GIST is less clear. Abdominoperineal resection (APR) or conservative surgery is the best treatment option. Imatinib mesylate, a tyrosine kinase inhibitor, has shown promising results in its management. We present a case of anorectal GIST diagnosed by computed tomography (CT) scan, magnetic resonance imaging (MRI), and colonoscopy with biopsy. The patient underwent abdominoperineal resection (APR) and was confirmed on histopathology to have anal canal GIST with tumor size more than 5 cm in maximum dimension and mitotic figures more than 5/50 high power field (HPF). The CD117—immunoreactive score—was 3+ in spindled cells. Therefore the patient was put on adjuvant imatinib mesylate 400 mg daily.